Radon concentration in Elazig houses and factories - Selcuk, AB; Yavuz, H; Koksal, EM; Ozcinar, B (Oxford Univ Press, 1998)
Rn-222 concentration was measured in Elazig houses and factories by forty-seven pairs of CR-39 detectors. Detectors were obtained from the laboratory of Cekmece Nuclear Research and Training Centre. They were etched and evaluated at the same laboratory. The measured concentrations were ranging between 17 and 184 Bq.m(-3) with a mean value of 47 Bq.m(-3).